PENGARUH KOMPETENSI, BUDAYA ORGANISASI DAN MOTIVASITERHADAP KINERJA PEGAWAI BALAI TEKNIK PENERBANGAN DIREKTORAT JENDERAL PERHUBUNGAN UDARA - ., Rinaldi; Yosepha, Sri Yanthy (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2024)
The Aviation Engineering Center of the Directorate General of Civil Aviation, based on the Government Agency Performance Accountability Report (GAPAR), obtained for 2021, there are 2 (two) targets with an average performanceachievement value â‰¤ 100%. Meanwhile, in 2022 there will be 1 (one) target with an average performance achievement value â‰¤ 100%. One of the reasons why this performance target has not been achieved is that competence, organizationalculture and motivation are not yet optimal. Study This aim for prove influence competence, culture organization, and motivation to performance employeeAviation Engineering Center of the Directorate General of Civil Aviation. Study This use approach quantitative, methods survey and analysis track. Population amount as many as 75 employees. In research This use saturated sampling technique, all member population used as the sample consisted of 75 employees. Data analyzed using SPSS version 25.0. results study showing that : competence influential direct positive and significant to motivation with big influence 0,415; culture organization influential direct positive and significant to motivation with biginfluence 0,330; competence influential direct positive and significant on performance with big influence 0,467; culture organization influential direct positive and significant to on performance with big influence 0,385; motivation influential direct positive and significant on performance with big influence 0,229. Implications, for increase performance employee of the Aviation Engineering Center of the Directorate General of Civil Aviation need done enhancement competence, carry out or apply culture good organization, and improve motivation for can get results more performance good.Â